دور البيانات الضخمة في إتخاذ القرارات الإستراتيجية - حميتي, نور الهدى; حملاوي, سكينة (University of Eloued جامعة الوادي, 2022)
The aim of our study is to keep pace with new insights about the use of big data in making strategic decisions by processing and analyzing a case study of companies (selected cases) that have adopted big data in their industries. We have found that big data is an important source of information and can provide a great deal of knowledge in making the decision to penetrate international markets, especially if the consumer sentiment is integrated with it. It leads to more specific decisions than traditional methods, and companies must incorporate big data into their strategy in international market entry patterns.
The role of big data in making strategic decisions
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: البيانات الضخمة، اتخاذ القرار، اختراق الاسواق الدولية; Big data, decision making, international market penetration